Genetic Characterization and Morphometric Variation of Siganus Canaliculatus Populations in the Waters of the Makassar Strait and Bone Bay as the Basis of Domestication Strategy - Sahabuddin, Sahabuddin; Indah Yani, Fitri; Jufri, Ady (Journal of Multidisciplinary Sustainability Asean, 2026)
Siganus canaliculatus represents a commercially important herbivorous reef fish with promising potential for aquaculture development in eastern Indonesia. Sustainable domestication requires comprehensive understanding of population genetic structure and morphological variability to ensure adaptive capacity and broodstock quality. This study aimed to characterize the genetic diversity and morphometric variation of S. canaliculatus populations in the Makassar Strait and Bone Bay as a scientific basis for domestication strategies. A comparative cross-sectional design was applied using mitochondrial DNA (COI) analysis and geometric morphometric techniques. A total of 102 specimens were sampled from both regions. Genetic diversity indices, fixation index (F_ST), analysis of molecular variance (AMOVA), principal component analysis (PCA), and discriminant function analysis (DFA) were performed. Results revealed moderate genetic diversity in both populations with significant genetic differentiation (F_ST = 0.118; p < 0.01). Morphometric analyses demonstrated clear shape divergence, particularly in body depth and head proportion, with 78.4% classification accuracy between populations. Concordance between genetic and phenotypic structuring indicates partial connectivity combined with local adaptation. These findings provide an integrative baseline for region-based broodstock selection and support sustainable domestication programs while maintaining genetic diversity and adaptive potential.